2022
DOI: 10.3389/fonc.2022.952480
|View full text |Cite
|
Sign up to set email alerts
|

Survival, treatment pattern, and treatment outcome in patients with cervical cancer metastatic to distant lymph nodes

Abstract: BackgroundCervical cancer with nodal involvement beyond the pelvis was considered as distant nodal metastasis in the previous International Federation of Gynecology and Obstetrics staging system. With the improvement of cancer-directed therapies, some of these patients can receive curative treatment. Classifying them as distant metastasis may result in underestimation of their prognosis as well as undertreatment. However, limited research has been conducted on the survival and treatment pattern in distant lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This study also provides additional insights regarding the factors that impact the utilization of IMT in patients with stage IVB cervical cancer compared with prior studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 19 , 21 , 24 , 25 , 30 , 48 , 49 , 50 , 51 , 52 , 53 ]. We found that patients with Medicaid insurance or no insurance, older age, or either distant lymph node or distant organ metastasis but not with both, and those treated at Non-Academic/Research Facilities or with CT + EBRT ± ICBT were significantly less likely to receive IMT.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This study also provides additional insights regarding the factors that impact the utilization of IMT in patients with stage IVB cervical cancer compared with prior studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 19 , 21 , 24 , 25 , 30 , 48 , 49 , 50 , 51 , 52 , 53 ]. We found that patients with Medicaid insurance or no insurance, older age, or either distant lymph node or distant organ metastasis but not with both, and those treated at Non-Academic/Research Facilities or with CT + EBRT ± ICBT were significantly less likely to receive IMT.…”
Section: Discussionmentioning
confidence: 78%
“…Surgery may or may not be used to treat cervical cancer. Despite these multiple therapeutic options, the prognosis for patients presenting with metastatic disease remains poor [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Definitive surgery is likely never a major consideration for patients with metastatic cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Three modes of treatment were given to cervical cancer patients in this study which included surgery, chemotherapy and radiotherapy, but none showed signi cant association with survival rate although the treatment details of each mode were not available for analysis and comparison. The three modes are the recommended treatment depending on extent of the cervical cancer (Lin et al, 2022). This study's ndings highlight the prevalence, survival outcome, factors associated with survival among cervical cancer patients for ve years from year 2017 to year 2022.…”
Section: Factors Associated With Survival Of Cervical Cancer Patientsmentioning
confidence: 77%
“…Lin et al. demonstrated that the deterioration of CSS rates was accompanied by an increase of T stage in stage IIIC2 ( P < 0.001) 30 . A Korean study reported that IIIC1r with pelvic side wall invasion (T3b) had approximately 3.8‐fold increased risk of mortality compared with those without this condition 14 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Lin et al demonstrated that the deterioration of CSS rates was accompanied by an increase of T stage in stage IIIC2 (P < 0.001). 30 A Korean study reported that IIIC1r with pelvic side wall invasion (T3b) had approximately 3.8-fold increased risk of mortality compared with those without this condition. 14 Additionally, many studies have consistently demonstrated that compared with stage IIIC1 with one to two PLNMs, stage IIIC1 with three or more PLNMs has significantly worse survival outcome.…”
Section: Comparison With Published Literaturementioning
confidence: 99%